2005
DOI: 10.2337/diabetes.54.11.3296
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase-1B Gene PTPN1

Abstract: Protein tyrosine phosphatase-1B negatively regulates leptin and insulin signaling, potentially contributing to hormonal resistance. We selected six tagging single nucleotide polymorphisms (SNPs) representing 18 common variants in the protein tyrosine phosphatase-1B gene (PTPN1) and tested their effect on serum leptin, body fat, and measures of insulin sensitivity and the metabolic syndrome in a large sample of normal female Caucasian twins (n ‫؍‬ 2,777; mean age, 47.4 ؎ 12.5 years) from the St. Thomas' U.K. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 43 publications
1
44
1
Order By: Relevance
“…The association between the PTPN1 gene and blood pressure was greatly in concordance with previous two reports (Cheyssac et al, 2006;Spencer-Jones et al, 2005). Both reports suggested that PTPN1 gene variants increase blood pressure.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The association between the PTPN1 gene and blood pressure was greatly in concordance with previous two reports (Cheyssac et al, 2006;Spencer-Jones et al, 2005). Both reports suggested that PTPN1 gene variants increase blood pressure.…”
Section: Discussionsupporting
confidence: 81%
“…We also identified the increased tendency of TG in homozygotes of rs6020612; the minor allele homozygotes were observed in only two individuals. Although this association was reported in other reports (Cheyssac et al, 2006;Spencer-Jones et al, 2005), the associated SNP had a higher frequency of minor allele homozygotes. Therefore, the association between PTPN1 and TG should be confirmed using other SNPs that have been previously reported.…”
Section: Discussioncontrasting
confidence: 47%
“…In a study of white subjects, Bento et al observed associations between several non-coding singlenucleotide polymorphisms (SNPs) positioned across PTPN1 and type 2 diabetes [2], whereas, in a study of Hispanic American subjects, Palmer et al observed associations between several of the same SNPs and insulin sensitivity and/or fasting glucose levels [3]. Subsequent replication studies of these initial reports have provided weaker or negative results for associations with type 2 diabetes or related phenotypes [4][5][6]. In the current study, we sought to determine whether SNPs in PTPN1 have a role in susceptibility to type 2 diabetes or obesity in the Pima Indian population of Arizona.…”
Section: Introductionmentioning
confidence: 85%
“…Therefore, it is possible that the nominal associations observed between SNPs in block 1 and insulin sensitivity in Pima Indians represent false associations due to multiple testing, rather than independent confirmation that this gene has a role in insulin action. Palmer et al also detected two SNPs (rs4811077 and Only non-diabetic subjects were used in this analysis p values were calculated under the additive model and were adjusted for: a age, sex and family membership b age, sex, per cent body fat and family membership c age, sex, per cent body fat, glucose disposal rate, 30-min glucose levels and family membership; analysis for 30-min insulin was done only in normal glucose tolerant subjects, n=186 d age, sex, per cent body fat, glucose disposal rate and family membership; analysis for acute insulin response was done only in normal glucose tolerant subjects, n (female/male): 1/1, 74 (17/57); 1/2, 91 (36/55); 2/2, 21 (8/13) EMBS, estimated metabolic body size [4] d SNPs associated with type 2 diabetes in white subjects [2] e SNPs associated with insulin sensitivity in Hispanic Americans [3] f SNPs associated with fasting glucose levels in Hispanic Americans [3] g SNPs associated with insulin sensitivity in female white twins [5] h SNPs associated with fasting insulin levels and glucose disappearance in white subjects from the HERITAGE Family study [11] i SNPs associated with type 2 diabetes in the Danish population [12] 1484insG) that were associated with the acute insulin response (AIR) [3], while Ukkola et al detected a single SNP (rs968701) that was associated with the AIR in white subjects [11]. None of the SNPs was associated with an AIR among 186 full-heritage Pima Indians with normal glucose tolerance (data shown for rs4811074 in Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…To control for population stratification bias, DZ twin pairs discordant for genotype were also used in a sibling transmission disequilibrium test (Sib-TDT) association analysis as described elsewhere [10,11].…”
Section: Snp Genotypingmentioning
confidence: 99%